Salivary Glands in Predatory Mollusks: Evolutionary Considerations - Ponte, Giovanna; Modica, Maria Vittoria (Frontiers in Physiology, 2017)
Many marine mollusks attain or increase their predatory efficiency using complex chemical secretions, which are often produced and delivered through specialized anatomical structures of the foregut. The secretions produced in venom glands of Conus snails and allies have been extensively studied, revealing an amazing chemical diversity of small, highly constrained neuropeptides, whose characterization led to significant pharmacological developments. Conversely, salivary glands, the other main secretory structures of molluscan foregut, have been neglected despite their shared occurrence in the two lineages including predatory members: Gastropoda and Cephalopoda. Over the last few years, the interest for the chemistry of salivary mixtures increased based on their potential biomedical applications. Recent investigation with -omics technologies are complementing the classical biochemical descriptions, that date back to the 1950s, highlighting the high level of diversification of salivary secretions in predatory mollusks, and suggesting they can be regarded as a pharmaceutical cornucopia. As with other animal venoms, some of the salivary toxins are reported to target, for example, sodium and/or potassium ion channels or receptors and transporters for neurotransmitters such as glutamate, serotonin, neurotensin and noradrenaline, thus manipulating the neuromuscular system of the preys. Other bioactive components possess anticoagulant, anesthetic and hypotensive activities. Here we overview available knowledge on the salivary glands of key predatory molluscan taxa, gastropods and cephalopods, summarizing their anatomical, physiological and biochemical complexity in order to facilitate future comparative studies on main evolutionary trends and functional convergence in the acquisition of successful predatory strategies. As with other animal venoms, some of the salivary toxins are reported to target, for example, sodium and/or potassium ion channels or receptors and transporters for neurotransmitters such as glutamate, serotonin, neurotensin and noradrenaline, thus manipulating the neuromuscular system of the preys. Other bioactive components possess anticoagulant, anaesthetic and hypotensive activities. Here we review available knowledge for different species belonging to key predatory Molluscan taxa, including gastropods and cephalopods, with the aims of highlighting main evolutionary trends both at the anatomical and at the physiological and biochemical level, and understanding the role of functional convergence in the definition of successful predatory strategies among different taxa.